2020
DOI: 10.1080/07391102.2020.1781694
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir (GS-5734) as a therapeutic option of 2019-nCOV main protease – in silico approach

Abstract: 2019-Novel Coronavirus (2019-nCOV), enclosed large genome positive-sense RNA virus characterized by crown-like spikes that protrude from their surface, and have a distinctive replication strategy. The 2019-nCOV belongs to the Coronaviridae family, principally consists of virulent pathogens showing zoonotic property, has emerged as a pandemic outbreak with high mortality and high morbidity rate around the globe and no therapeutic vaccine or drugs against 2019-nCoV are discovered till now. In this study, in sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 44 publications
4
43
0
2
Order By: Relevance
“…Remdesivir inhibits production of viral RNA and the mechanism how it is happening is not yet well explained. Some of its metabolites are interfering with viral RNAdependent RNA polymerase, while remdesivir can interact with viral protease [32], which interaction we have analyzed here. Activity of retroviral proteases is one of the critical steps in viral replication as this enzyme cleaves newly synthetized viral poly proteins to create mature protein components of an infectious virion.…”
Section: Interaction Between Remdesivir and Retroviral Protease Proteinsmentioning
confidence: 99%
“…Remdesivir inhibits production of viral RNA and the mechanism how it is happening is not yet well explained. Some of its metabolites are interfering with viral RNAdependent RNA polymerase, while remdesivir can interact with viral protease [32], which interaction we have analyzed here. Activity of retroviral proteases is one of the critical steps in viral replication as this enzyme cleaves newly synthetized viral poly proteins to create mature protein components of an infectious virion.…”
Section: Interaction Between Remdesivir and Retroviral Protease Proteinsmentioning
confidence: 99%
“…It is clearly showed that the majority of interactions are electrostatic and colored in violet. Remdesivir interacts with the viral RNA-dependent RNA polymerase, but some articles stated that remdesivir is a protease inhibitor [ 46 , 47 ], so we decided to dock remdesivir into the main protease. The resulting CDOCKER energy and GOLD score value of remdesivir is very low, demonstrates that remdesivir is not a protease inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the docking and molecular dynamics were performed for ligands such as Hydroxychloroquine, Chloroquine [15,16], Remdesivir [17][18][19], N3 [20] and 11b [21], to serve as an energy parameter to assess the a nity of the other ligands -positive control. The structure of the ligands with possible 3CLpro inhibitory activities, derived from the Virtual Screening carried out by HOFMARCHER [14] were obtained from the ZINC database (https://zinc.docking.org/).…”
Section: Protein Structurementioning
confidence: 99%
“…In December 2019 in Wuhan city in China, local doctors identi ed a new coronavirus as the causative agent of a severe acute respiratory syndrome type [1] later called Coronavirus Disease 2019 (COVID- 19). COVID-19 is a disease caused by SARS-CoV-2 [2], SARS are commonly characterized by high fever, malaise and non-productive cough and in some severe cases can cause generalized interstitial in ltration of the lungs, leading to the cases of intubation and mechanical ventilation of those affected [3].…”
Section: Introductionmentioning
confidence: 99%